Characteristics of root‐associated bacterial community and nitrogen biochemical properties of two Japonica rice cultivars with different yields. (29th December 2021) - Dong, Hangyu; Sun, Haoyuan; Jiang, Linlin; Ma, Dianrong; Fan, Shuxiu
Abstract: Root‐associated microbiomes play pivotal roles in rice plant nutrition and productivity. We studied how the Liaoxing 1 and Akitakomachi rice cultivars, which are characterized by high and low yields, respectively, modified the nutrient content, enzymatic activities in the rhizosphere, and bacterial community structure in the root endosphere, rhizosphere, and bulk soil with and without nitrogen application. Rice genotype and nitrogen application amount are both essential driving factors for changes in the nutrient content, enzymatic activities, and bacterial community. Bacterial community structure varied significantly across the three root‐associated compartments, and rhizosphere and bulk soil harbored significantly higher diversity and richness of bacteria than root endophytes. Bacterial communities in the root endosphere are mainly structured by rice cultivars. Nitrogen fertilization application influenced the compositions and functions of bacterial groups across the three compartments. Prolixibacteriaceae, as nitrogen‐fixing bacteria, were significantly enriched in the rhizosphere, and the relative abundance in the rhizosphere of the high‐yield cultivar was higher than that of the low‐yield cultivar. Rice genotype and nitrogen application amount are both essential driving factors for changes in nutrient content and enzymatic activities. In this study, it was found that the higher available nitrogen content and soil enzymatic activities in the rhizosphere of the high‐yield rice cultivar promoted rice nitrogen use, and they ultimately formed a positive feedback loop. Our results indicated that root‐associated bacterial communities combined with soil enzymatic activities strengthen the transformation of nitrogen nutrients, suggesting that the interactions could represent a mechanism for enhancing rice yield. Abstract : Root‐associated bacterial community combined with soil enzymatic activities strengthen the transformation of nitrogen nutrients, suggesting that the interactions could represent a mechanism for enhancing rice yield.